2007
DOI: 10.1111/j.1365-2109.2007.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and carcass composition of giant freshwater prawn, Macrobrachium rosenbergii (De Man), fed different isonitrogenous and isocaloric diets

Abstract: A feeding experiment was conducted for 135 days to observe the effect of different isonitrogenous (35% crude protein) and isocaloric (385 kcal) diets on the growth and carcass composition of giant freshwater prawn, Macrobrachium rosenbergii (De Man 1879). Three experimental diets (ED1, ED2 and ED3) were prepared using locally available ingredients. These diets differed mainly in terms of percent contribution of major protein sources such as fish meal, soybean meal, groundnut oil cake and mustard oil cake. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
6
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
5
21
6
3
Order By: Relevance
“…The survival rates of the present study also higher compared to the survival rate 64%–78% reported by Gupta et al. (). Most of the prawn farmers in Bangladesh stock postlarvae for grow‐out but in the study we have stocked juveniles.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The survival rates of the present study also higher compared to the survival rate 64%–78% reported by Gupta et al. (). Most of the prawn farmers in Bangladesh stock postlarvae for grow‐out but in the study we have stocked juveniles.…”
Section: Discussioncontrasting
confidence: 62%
“…Low‐lying rice fields modified by raising dikes locally (called ghers) are widely used for integration of shrimp and prawn cultivation with fish, rice and vegetables. Relatively high market values, fast growth, salinity and temperature tolerance and disease resistance have led increasing numbers of farmers to convert rice fields to ghers for freshwater prawn farming (Roustaian, Kamaruddin, Omar, Saad & Ahmad, ; Gupta, Sehgal & Sehgal, ; Ahmed, Allison & Muir ). During 2013–2014 Bangladesh earned US$ 528 million by exporting 47,635 MT of shrimp and prawn, with a 30% contribution from prawns (DoF ).…”
Section: Introductionmentioning
confidence: 99%
“…Although no significant differences in growth rate were observed by Gupta et al [29] for Macrobrachium rosenbergii juveniles fed different experimental isonitrogeneous and isocaloric diets, which varied in terms of percent contribution of major protein sources (fish meal, soybean meal, groundnut oil cake and mustard oil cake), some differences were observed in the present work. Figure 1 shows the variation in weight for the three groups of shrimps, fed for 90 days (Figure 1).…”
Section: Results and Conclusioncontrasting
confidence: 47%
“…Otherwise Onyia et al (2013) reported that moisture content of wild Heterobranchus bidorsalis was lower than cultured one. The difference trend of moisture content in wild and cultured fish could be as a result of age, diet and environmental factors (Gupta et al, 2007). …”
Section: Moisture Contentmentioning
confidence: 99%